Bibliometric Analysis and Model Development of the Digital Twin Applicability at All Stages of the Asset Lifecycle - Krhač Andrašec, Eva; Urh, Benjamin (Vloga naprednih tehnologij v inženiringu poslovnih sistemov, 2025)
In today's business environment, effective asset management is crucial for creating value in organizations. We face questions such as what it means to have a Digital Twin (DT) for physical assets? What is the role of DT in asset management (Errandonea idr., 2020)? The objective of the chapter is to provide a comprehensive overview of the current applicability of the digital twin (DT) in all phases of the asset lifecycle. The chapter contributes to the discussion of this issue by systematically reviewing literature, identifying key findings, and analyzing the role of DT in asset management. The methodology for solving includes thorough research of existing scientific and professional sources on DT, followed by synthesizing the obtained data to understand the role of DT in asset management. The results serve as a basis for preparing analytical findings, enabling the organization to create value from digital twin-based assets.